2018
DOI: 10.1038/s41598-018-34901-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A3 is required for normal lung development and survival following influenza infection

Abstract: Serum amyloid A (SAA) proteins are a family of acute phase apolipoproteins implicated to directly modulate innate and adaptive immune responses. However, new studies comparing endogenous SAAs and recombinant forms of these proteins have questioned the function of SAA in inflammation and immunity. We generated SAA3 knockout mice to evaluate the contribution of SAA3 to lung development and immune-mediated lung disease. While SAA3 deficiency does not affect the generation of house dust mite-induced allergic asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…Moreover, there is a strong correlation between elevated blood as well as sputum SAA levels and asthma prevalence and/or allergic rhinitis and disease severity [23,24,212]. As described above, the ability of SAA1 to adopt different oligomeric states (monomers and oligomers) [202] or to transport retinols and related molecules [187,188] might serve to scavenge and sequester essential vitamins (or even nutrients) to deter pathogen growth at mucosal surfaces [215] and may thus have important functional implications for promoting local inflammation. Considering that SAA is increased in allergic asthma [23,24], it remains to be established whether SAA functions as an adjuvant and/or interacts directly with environmental airborne proteins to promote allergic sensitization.…”
Section: Serum Amyloid Amentioning
confidence: 99%
“…Moreover, there is a strong correlation between elevated blood as well as sputum SAA levels and asthma prevalence and/or allergic rhinitis and disease severity [23,24,212]. As described above, the ability of SAA1 to adopt different oligomeric states (monomers and oligomers) [202] or to transport retinols and related molecules [187,188] might serve to scavenge and sequester essential vitamins (or even nutrients) to deter pathogen growth at mucosal surfaces [215] and may thus have important functional implications for promoting local inflammation. Considering that SAA is increased in allergic asthma [23,24], it remains to be established whether SAA functions as an adjuvant and/or interacts directly with environmental airborne proteins to promote allergic sensitization.…”
Section: Serum Amyloid Amentioning
confidence: 99%
“…Serum amyloid A (SAA) is an acute-phase protein during infection and inflammation [21,22]. Emerging evidence showed that SAA could be a potential marker for virus infection, such as Epstein-Barr virus [23], cytomegalovirus infection [24], hepatitis C virus [25], as well as influenza infection [26]. These aforementioned data have suggested that SAA could be an important biomarker in virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whether SAA is not just a marker but also an active participant in disease is intensely investigated, and numerous, sometimes conflicting, functions have been ascribed to this mysterious protein. The current consensus is that SAA modulates adaptive and innate immunity and mediates lipid transport during inflammation [ 1 •, 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%